The balance between text and image in TV news editing The example of the 8:00 PM news bulletin on NRT & K24 Analytical and comparative research (Raparin Journal of Humanities (RJH), 2023)
This research entitled (The Balance between text and image in TV news editing) is an attempt to clarify the balance between two main elements, which are text and image in the TV news editing process on Kurdish satellite channels. The research explores how TV channels use text-image balance in news broadcasting.      The main objective of this study is exploring the methods of balancing between text and image in news editing. The researcher relies on descriptive and content analysis methods to achieve its objectives. The research follows some methods of collecting data including monitoring and note-taking, interviews, surveys.       The main finding of this research is: K24 keeps balance between text and image in news stories related to political, economic, partisan, governmental, military, environmental, and religious. In contrast, NRT follows balancing only in news stories involving governmental, partisan, and organizational. The results show that K24 is using balance more than NRT. This research also shows that both channels are working on that breaking news and current affairs by using description and showing the images when available. In their news editing they show the same angles and frames that are new and they use different sources. They use more (Cut effect) in editing, which is one of the crucial and suitable effects of news editing on TV.